(untitled) (Bangladesh Journal of Anatomy, 2015)
Objective: To explore the perception of intern doctors and postgraduate students of Neurology, Neurosurgery and Psychiatry about neuroanatomy education at the undergraduate and postgraduate levels in Bangladesh. Participants and methods: Eight intern doctors and fourteen postgraduate students were selected on the basis of their willingness to participate in the study. The intern of a public medical college hospital who almost completed their training and final part postgraduate students of Neurology, Neurosurgery and Psychiatry of different medical institutions of Dhaka were invited for the study. Qualitative research methods involving two focus group discussions (FGDs) were used. FGDs were modelled using some preselected agenda. The discussions were audiotaped and handwritten transcripts were analysed for identifying themes representing the perception. Results: Neuroanatomy was perceived as a difficult but important subject by the participants. Inappropriate timing, as well as the limited use of radiological images, visual aids, clinical correlation and a lack of discipline-specific approach were perceived as the causes of the difficulties. The suggested ways of improving better understanding included enhanced functional, clinical and radiological orientation, and increased use of multimedia and online resources in the teaching-learning of neuroanatomy. Conclusion: The perception of intern doctors and postgraduate students of Neurology, Neurosurgery and Psychiatry about their neuroanatomy education indicates the need for redesigning teaching-learning at the undergraduate and postgraduate levels. Enhancement of radiological images, 3-D visual aids, clinically-oriented and discipline-specific approach in neuroanatomy teaching-learning may be helpful in applying relevant knowledge and skills in clinical practices. Bangladesh Journal of Anatomy July 2015, Vol. 13, No. 2, pp. 46-56